VD_FINDINFO HC / 2010 / 48 vom 27. November 2009 - VD Tribunal cantonal (2009)
RÉSILIATION, CONTRAT DE TRAVAIL, JOUR DÉTERMINANT, FARDEAU DE LA PREUVE | 8 CC, 335 CO, 451 ch. 2 CPC, 452 al. 2 CPC, 471 al. 3 CPC, 46 LJT